TrendPowerTool: A lookup tool for estimating the statistical power of a monitoring program to detect population trends. Issue 7 (7th May 2021) - Weiser, Emily L.; Diffendorfer, Jay E.; Lopez‐Hoffman, Laura; Semmens, Darius; Thogmartin, Wayne E.
Abstract: A simulation‐based power analysis can be used to estimate the sample sizes needed for a successful monitoring program, but requires technical expertise and sometimes extensive computing resources. We developed a web‐based lookup app, called TrendPowerTool (https://www.usgs.gov/apps/TrendPowerTool/ ), to provide guidance for ecological monitoring programs when resources are not available for a simulation‐based power analysis. TrendPowerTool is implemented through the shiny package in R, but is accessible through a webpage without the need for users to install any software. By drawing on results of 1.4 million scenarios that we simulated on a supercomputer, TrendPowerTool quickly and easily provides an estimate of the statistical power to detect a population trend of a particular magnitude with a planned monitoring program, based on user‐specified parameters for the monitoring design and population of interest. TrendPowerTool provides a user‐friendly interface that retrieves results instantaneously, facilitating the important step of conducting a power analysis when designing monitoring programs. Abstract : New web‐based lookup tool provides an accessible way to inform the design of programs to monitor population trends.